FEATURES OF THE FORMATION OF MANAGEMENT CAPITAL IN THE CONDITIONS OF INTELLECTUALIZATION OF SOCIAL-LABOR RELATIONS OF THE MODERN BUSINESS SPACE - N. A. Tyukhtenko (Aktualʹnì Problemi Rozvitku Ekonomìki Regìonu)
The article is devoted to the formation of managerial capital in the modern business space, which plays an important role in the activities of economic entities at the micro and macro levels. The importance of the processes of intellectualization of production relations of economic entities is proved, especially in the context of the formation of competitive human capital. Based on the analysis of theoretical approaches, the essence and main components of managerial capital as the intellectual capital of the management team are outlined. The author analyzes the concept of intellectual capital of business space, which is presented as its intangible asset (values) that can increase the market value and competitiveness of organizations. A modern view of intellectual capital has made it possible to distinguish its three components: human, organizational and client (partner, stakeholder) types of capital. It is proved that intellectualization of the business environment is an objective condition for economic management in the context of finding ways of economic growth through highly professional teamwork of the enterprise's personnel in the context of a professional management system and formation of managerial capital. The author's own vision of the structure of management capital is proposed, consisting of human capital of the management team, its emotional capital and socio-cultural capital (management culture). The human capital of the management team is considered as a system that includes education and experience, health, creativity, corporate knowledge, understanding of external and internal information. Attention is focused on the basic principles of forming the emotional capital of the organization and the management team through the presence of emotional intelligence. The socio-cultural capital is proposed to be considered in the form of managerial culture, which includes the capital of social and labor relations and communication; norms and values; motivation; equality, diversity and inclusiveness of the management team. The author substantiates the impact of managerial capital on the intellectualization of social and labor relations, which provides for the possibility of improving the quality of working life of each employee and achieving success of economic entities in the face of complex transformational challenges. The category of “quality of working life” is considered as the main result of the functioning of a professional management system and the corresponding management capital. The author proposes a system of factors influencing the quality of working life, which are caused by the intellectualization of social and labor relations in the modern business space.